RESPON BEBERAPA GENOTIPE TANAMAN PADI GOGO LOKAL SUMATRA BARAT TERHADAP PEMBERIAN PUPUK ORGANIK CAIR PADA INCEPTISOL - Reda, Abdul; Ediwirman, Ediwirman; Ernita, Milda; Jamilah, Jamilah; Sunadi, Sunadi (Percetakan Umi Toaha Makassar, 2024)
Upland rice is a type of rice that has the potential to be developed in the South Solok area on Inceptisol dry land. Several types of upland rice were tested with the application of liquid organic fertilizer to obtain the best interaction between upland rice types and liquid organic fertilizer concentrations on growth and yield. The experiment was conducted on the inceptisol land of the Central Seed Center, South Solok District Agriculture Office, altitude of 980 meters above sea level, from July to December 2022. The experiment was arranged using a Randomized Block Design, a factorial treatment consisting of two factors. The first factor is the genotype of upland rice, namely; Guliang Tanda Merah, Rokan, Sibawang, and Simaritik. The second factor is the concentration of liquid organic fertilizer namely; 0, 20, 40, and 60 ml l-1, each experimental unit consisted of 3 replicates. observed data were analyzed using the F test if the calculated F is greater than the F table then proceed with the DNMRT test at the 5% level. Based on the experimental results, it can be concluded that the interaction of genotypes of upland rice and POC 20 ml.l 1 on the variable number of panicle grains. Provision of 60 ml.l-1 POC increased plant height growth, number of productive tillers, flowering age, harvest age, flag leaf length, number of panicles, panicle length, number of grains per hill, number of empty grains, number of grains per hill, percentage of empty grain, grain weight per hill of upland rice plants. upland rice genotype, Guliang Tandai Merah is a genotype that has high productivity in all observed variables